2002
DOI: 10.1097/00007632-200202150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Recombinant Human Bone Morphogenetic Protein-2 Using a Compression-Resistant Matrix in Posterolateral Spine Fusion in the Rabbit and in the Non-Human Primate

Abstract: The new compression-resistant biphasic ceramic phosphate/collagen sponge matrices were biologically compatible with recombinant human bone morphogenetic protein 2 bone formation, resulted in biomechanically stiffer fusion masses than autograft, better space maintenance than plain collagen sponges, and improved handling and radiographic resorption properties over the ceramic carriers previously tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(77 citation statements)
references
References 11 publications
1
74
0
2
Order By: Relevance
“…Some BMPs can induce bone formation in mice, rats, rabbits, sheep, dogs, monkeys, and baboons. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Purified BMP-2, BMP-4, and BMP-7 have been used in human clinical cases to repair resistant nonunions and segmental defects of long bones. [19][20][21][22][23] In a previous study, the ability of recombinant human BMP-2, BMP-3, BMP-4, BMP-5, BMP-6, and BMP-7 to stimulate DNA synthesis was compared in cultures of periosteal cells and epiphyseal and sternal chondrocytes of embryonic chick.…”
Section: Introductionmentioning
confidence: 99%
“…Some BMPs can induce bone formation in mice, rats, rabbits, sheep, dogs, monkeys, and baboons. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Purified BMP-2, BMP-4, and BMP-7 have been used in human clinical cases to repair resistant nonunions and segmental defects of long bones. [19][20][21][22][23] In a previous study, the ability of recombinant human BMP-2, BMP-3, BMP-4, BMP-5, BMP-6, and BMP-7 to stimulate DNA synthesis was compared in cultures of periosteal cells and epiphyseal and sternal chondrocytes of embryonic chick.…”
Section: Introductionmentioning
confidence: 99%
“…Previous preclinical experiments with rhBMP-2 implanted in animals showed that successful results with rhBMP-2 were dependent on concentration, not delivered dose. 22 Although it is unknown if longer soaking times would benefit clinical outcomes in an ALIF application, longer soaking times may help to maximize the amount of rhBMP-2 at the local site in environments that may be exposed to increased compressive loads.…”
Section: Discussionmentioning
confidence: 99%
“…Existem diferentes tipos de carreadores, com diferentes tipos de resposta (Zegzula et al, 1997;Suh et al, 2002), sendo ainda necessĂĄrio esclarecer problemas como combinação, biodisponibilidade, difusibilidade e espĂ©cie (Lane, 2001). O carreador incorporado ao produto utilizado tratase da hidroxiapatita reabsorvĂ­vel microgranular que, segundo Granjeiro et al (1992), permite reabsorção pelo mecanismo de fagocitose e possui alto grau de pureza.…”
Section: Discussionunclassified
“…VĂĄrios tipos de compostos de hidroxiapatita, reabsorvĂ­veis ou nĂŁo, tĂȘm sido testados como carreadores com resultados satisfatĂłrios (Suh et al, 2002;Den Boer et al, 2003). O mesmo carreador empregado no experimento foi utilizado em associação Ă  BMP (Lima, 2002), ao osso bovino inorgĂąnico (Costa Filho et al, 2001), ou Ă  matriz Ăłssea orgĂąnica (Braz et al, 2003), aparentemente sem interferĂȘncia com a produção de osso.…”
Section: Discussionunclassified